IMPORTANCE OF LABORATORY PARAMETERS IN THE DIAGNOSTICS OF COMPLICATED LIVER ECHINOCOCCOSIS - Z.A. AZIZZODA; K.M. KURBONOV; K.R. RUZIBOYZODA; N.A. RASULOV; S.G. ALI-ZADE (Avicenna Tajik State Medical University, 2019)
Objective: To determine the role of laboratory parameters for the study of early diagnosis of liver echinococcosis (LE) complications. Methods: Carried out the results of a study of 147 patients with complicated LE - suppuration of echinococcal cysts (n=50) and mechanical jaundice (n=97). As a result of a general blood analysis for diagnosing complications of LE were studied biochemical analyzes and indicators of endogenous intoxication. Results: The results of the study showed that in patients with complicated LE - suppuration and mechanical jaundice, noticed an increase content of leukocytes in 67.3%, of eosinophils in 42.9% and accelerated ESR in 57.8% of cases. The leukocyte intoxication index (LII) in patients with suppurative echinococcal liver cysts was 4.3±0.06 units. In patients with mechanical jaundice, an increase in the activity of ASAT and ALAT was observed up to 52.4±0.07 and 64.3±0.05 IU/L, respectively. In addition, patients showed an increase in the level of urea (7.8±0.05 mmol/L) and creatinine (128.4±0.04 μmol/L). In severe cases of jaundice indicators of bilirubin exceeded 190 μmol/L, diene conjugates increased to 1.86±0.074 nmol/L, malondialdehyde to 8.15±0.4 μmol/L, and medium mass molecules to 0.5±0.04 c.u./L, procalcitonin - up to 5.6±0.04 ng/mL, C-reactive protein - up to 175.3±9.8 mg/L. Conclusion: Some indicators of the general and biochemical analysis of blood, as well as indicators of endogenous intoxication, can be very informative for the early diagnosis of complications of liver echinococcosis and determine the functional state of the liver. Laboratory indicators of functional state of the liver and the common state of the patients helps to choose the most rational surgery tactics, and thereby reduce the percentage of postoperative complications and mortality among these severe categories of patients.